The Effect of Product Quality and Distribution Channels on Repurchasing Intention - Ferdian Adeosandi; Eka askafi; Nisa Mutiara (Jurnal Manajemen Industri dan Logistik, 2023)
This research was motivated by the Covid-19 pandemic, which directly changed people's lifestyles. The purposes of this study were: (1) To determine the effect of product quality and distribution channels on repurchase intentions in users of the application's food ordering feature to become an online driver in the City of Kediri (2) To determine consumer satisfaction can mediate the effect of product quality on repurchase intentions in consumers. Application messaging feature users become online drivers in the city of Kediri. The research uses a quantitative approach with a questionnaire instrument. The results obtained from this study are Product quality partially has no effect on repurchase intentions, Distribution channels partially have a significant positive impact on repurchase intentions, partially, consumer satisfaction has a positive on repurchase intentions, Product quality has a positive effect on consumer satisfaction, and distribution channels have a positive impact on consumer satisfaction